Ekspektasi, Realisasi Dan Negosiasi Tourism Reborn Di Masa Pandemi Dalam Pariwisata Bali - Ida Ayu Devi Arini; Ida Bagus Gede Paramita; Komang Alit Triana (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2020)
The corona virus pandemic is a major blow that has rocked tourism sector, especially in Bali. This resulted in hotels and restaurants as well as tourist accommodations that stopped operating. However, along with the new normal policy, many tourist destinations are ready to receive tourist visits again. The government has also implemented a recovery strategy to accelerate the revival of Bali tourism by adopting policies which are able to accommodate the wishes of tourism actors. The purposes of writing this scientific article are a) to convey the hopes of tourism actors regarding the acceleration of the revival of Bali tourism; b) to observe the synchronization of government policies with tourism actors related to accelerating the recovery of Bali tourism; c) to convey hopes and suggestions so that the policies implemented by the government accommodate the interests of tourism actors. The data collection method in this article is literature study. The results which are obtained from the writing of this scientific article are knowing the expectations of tourism actors in relation to the policies implemented by the government to side with the acceleration of the revival of Bali tourism. Keywords: Expectation, Realization, Negotiation, Tourism Reborn